Digital Activism and Collective Mobilization: A Narrative Review of Social Identity, Group Efficacy, and the SIMCA Framework - Ali, Muhammad Nur (Yayasan Sinergi Kawula Muda, 2025)
Collective action has long been driven by social psychological mechanisms, particularly collective identity and group efficacy. This narrative review examines the interplay of identity, emotion, and structural conditions in predicting participation in collective mobilization. Drawing on empirical findings from multiple cross-national studies, the review integrates qualitative and quantitative insights to understand how emotional catalysts and digital narratives reinforce collective identification. The methodology involved a systematic review of studies indexed in Scopus, Web of Science, and Google Scholar, using key terms such as